BUDAYA PEMILIHAN MENU MAKANAN PADA ANAK LEUKEMIA - Indriatie .; nurhasanah . (JURNAL PENELITIAN KESEHATAN, 2015)
In Children Inpatient Hospital Dr Soetomo, leukemia in the group of ten main diseases. Theresearch objective was to determine the selection of culture on children's diet leukemia in Hospital DrSoetomo, include: trust, mother's knowledge about nutrition, food social function, and preferences.This study is a qualitative study, which used a phenomenological approach. The unit of analysisin this study were all mothers or families and child leukemia patients who were treated at room Bona IHospital Dr. Soetomo in November 2014. Respondents who studied a number of 5 patients and theirfamilies. Variable is cultural research on children's food menu selection leukemia. Data was collectedthrough in-depth interviews or interviews indept interview guide was used in the study subjectshereinafter referred to as informants.Leukemiain children with a history of eating mostly fast food in the form of instant noodles in thediet of their daily, over a long time. In shaping the culture of food on the menu selection since earlychildhood, takes the role of the parents, especially 'the mother to give knowledge about healthy foodaccording to the child's nutritional needs, maximizing togetherness in the family, and increaSingthe role ofthe family to solve the problems of malnutrition in children, familiarize the children and members otherfamilies to choose a healthy diet and natural.Keywords: Cultural selecting food menu, leukemia.